DESCRIPTION OF IMMATURE STAGES OF POLYMERIUS CHILENSIS (LAPORTE, 1 8 3 4 ) (COLEOPTERA: RHIPICERIDAE) (Acta Entomológica Chilena, 2022)
Through the study of exuviae, the last instar larva and some characters of the pupa of Polymeriuschilensis (Laporte, 1834) (Coleóptera: Dascilloidea: Rhipiceridae) are described. The larva has a threesegmented antenna, a subantennal protuberance, maxillary cardines well developed, three segmentedmaxillary palpi, two segmented labial palpi, one seta on tarsungulus and lacks urogomphi and the eighthpair of abdominal spiraculae. The pupa is characterized by dorsal and ventral tubercles of the ninthabdominal segment and a marginal ridge in the seventh abdominal ventrite. The exuviae were foundwithin a subterranean chamber together with a female imago of Polymerius chilensis and a cicada nymphremains, verifying the parasitic condition of the larvae of Rhipiceridae.
Keywords: Coleóptera, Rhipiceridae, Polymerius chilensis, larvae, pupa, description